Study on Seismic Performance of Improved High-Strength Concrete Pipe‐Pile Cap Connection - Zhijian Yang; Guochang Li; Bo Nan (Advances in Materials Science and Engineering)
Four prestressed high-strength concrete pile- (PHC pile-) pile cap connections under low-cycle loading were tested to study the test phenomena, failure modes, hysteretic performance, ductility, and bearing capacity. The PHC piles were reinforced with steel fiber and deformed bars and CFRP. The tests results showed that the connections were damaged by bending. The concrete of the caps were squeezed to be crushed. The concrete of connection was crushed and formed a hinge joint that resulted in the connection rotating unrestricted, and the rotation capacity of connection increased. The PHC pile reinforced with steel fiber and deformed bars can improve the displacement ductility of the connections. The finite element software ABAQUS was used to simulate the nonlinear behavior of pile-cap connections. The prediction agreed relatively well with the experimental results. The stress and strain of specimens were studied. The connections should be designed with enough rotating capacity and make sure the cap will not be damaged by squeezing or prying due to the rotation of pile end.